PEMANFAATAN AMPAS PADAT BREM CAIR MENJADI GULA CAIR - Sinta Citra Pertiwi, Ida Ayu; Wrasiati, Luh Putu; Arnata, I Wayan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
This study aims to 1) determine the effect of comparison between brem dregs flour with a solution of hydrochloric acid (HCl) and a long hydrolysis of the characteristics of liquid sugar produced, 2) determining the ratio of brem dregs flour with a solution of hydrochloric acid (HCl) and long hydrolysis to produce the characteristic of best sugar liquid. This experiment was factorial experiment using a randomized block design (RAK) with two factors. The first factor is the ratio between Brem dregs flour with a solution of hydrochloric acid (HCl) 0,75% consists of three levels, namely; 1:4, 1:6 and 1:8. The second factor is the length of hydrolysis which consists of three levels ie; 10 minutes, 20 minutes and 30 minutes. Thus obtained 9 treatment combinations were grouped into two, based on the execution time so that obtained 18 experimental units. The variables analyzed were the starch content, ash content, reducing sugar, yield and total dissolved solids. Objective data were analyzed by analysis of variance followed by Duncan test. The results showed that the brem dregs flour with a solution of hydrochloric acid (HCl) and a long hydrolysis significant  effect on the starch content, reducing sugar, yield and total dissolved solids, while the ash content not significant. Interactions between treatment comparisons brem dregs flour with a solution of hydrochloric acid (HCl) and a long hydrolysis very significant effect on the starch content, reducing sugar, yield and total dissolved solids. Handling of comparison among brem dregs flour with a solution of hydrochloric acid (HCl) 1:4 and hydrolysis for 30 minutes will produce liquid sugar product with the best  quality in accordance with SNI 01-2891-1992 about liquid sugar syrup composition based on the value of reduction sugar namely ash content <1% in accordance with the SNI, reduction sugar 33,89 mg/l, yield 167,77% and total dissolved solids 49% brix except  the starch content of 1,20%. Keywords : acid hydrolysis, brem dregs, hydrochloric acid, liquid sugar
Keywords: 120